2020
DOI: 10.1021/acs.chemrestox.0c00328
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan- and Tolvaptan-Metabolite-Responsive T Cells in Patients with Drug-Induced Liver Injury

Abstract: Tolvaptan is an effective drug for the treatment of autosomal dominant polycystic kidney disease, but its use is associated with a significant risk of liver injury in a small number of patients. Herein we describe the presence of tolvaptan- and tolvaptan-metabolite-responsive T cell clones within the peripheral circulation of patients with liver injury. Drug treatment of the clones resulted in a proliferative response and secretion of IFN-γ, IL-13, and the cytolytic molecule granzyme B. Future work should expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“… 39 Furthermore, in vitro evidence has suggested that liver injury may be mediated by tolvaptan-induced T-cell activation and the subsequent release of specific cytokines, especially interferon-γ, interleukin-13 and granzyme-B. 40 Transcriptomic analysis using Collaborative Cross mice showed that tolvaptan may contribute to liver oxidative stress, mitochondrial dysfunction and activation of innate immunity. Interestingly, susceptibility to liver injury correlated with the mRNA expression and plasma levels of secretory leukocyte peptidase inhibitor, indicating its potential role as a predictive factor of hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“… 39 Furthermore, in vitro evidence has suggested that liver injury may be mediated by tolvaptan-induced T-cell activation and the subsequent release of specific cytokines, especially interferon-γ, interleukin-13 and granzyme-B. 40 Transcriptomic analysis using Collaborative Cross mice showed that tolvaptan may contribute to liver oxidative stress, mitochondrial dysfunction and activation of innate immunity. Interestingly, susceptibility to liver injury correlated with the mRNA expression and plasma levels of secretory leukocyte peptidase inhibitor, indicating its potential role as a predictive factor of hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The application of TVP is associated with a risk of liver injury in a small portion of ADPKD patients. 22 To examine the potential hepatotoxicity of the benzodiazepine derivatives, wild-type C57BL/6 mice were treated with 5 mg/kg compound 25 or TVP once daily for 12 consecutive days. Serum alanine aminotransferase (ALT) was selected as a surrogate marker to evaluate the potential hepatotoxicity.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Similarly, Tolvaptan has some effect on T-cells, although this has been correlated with the adverse effect of the drug onto the liver [ 72 ].…”
Section: Vra and Egfr Reductionmentioning
confidence: 99%